An Exploration of the Utility of a Knowledge Utilization Framework to Study the Gap Between Reading Disabilities Research and Practice (Alberta Journal of Educational Research, 2012)
This pre-pilot study explored the usefulness of a knowledge utilization framework comprised of Knott and Wildavsky’s (1980) seven stages of knowledge use and Stone’s (2002) three routes to knowledge use to investigate the gap between reading disabilities research and teachers’ self-reported use of that research. Semi-structured interviews of ten elementary school teachers were undertaken. A qualitative analysis of the interview data indicated that the framework was effective for categorizing and interpreting the interview responses. Findings indicated that a divide between research and reported practice potentially begins with an inadequate reception of research, and that a divide is exacerbated by limited reading and implementation of research knowledge by teachers. The knowledge utilization framework also assisted in identifying obstacles to teachers’ reported use of research. These obstacles were successfully categorized according to the variables of supply, demand, and context. The combined framework of knowledge utilization has potential for studying the use of research by teachers.   Cette étude pré-pilote a exploré l’utilité d’un cadre de l’emploi des connaissances - comprenant les sept étapes de l’emploi des connaissances de Knott et Wildavsky (1980) et les trois routes de l’emploi des connaissances de Stone (2002) – dans l’étude de l’écart entre la recherche portant sur les déficiences en lecture d’une part, et l’emploi que les enseignants affirmaient faire de cette recherche d’autre part. Nous avons effectué des interviews semi-structurées auprès de dix enseignants de l’élémentaire. Une analyse qualitative des données d’entrevue a indiqué que le cadre était efficace dans la catégorisation et l’interprétation des réponses découlant des interviews. Les résultats indiquent qu’un fossé peut commencer à se creuser entre la recherche et l’application qu’on dit en faire quand la recherche n’est pas suffisamment accueillie, et que ce fossé s’élargit si la mise en œuvre que font les enseignants de la recherche et des connaissances qui en découlent est limitée. Le cadre de l’emploi des connaissances a également été utile dans l’identification des obstacles à l’utilisation que les enseignants déclaraient faire de la recherche. On a réussi à classer ces obstacles en fonction de trois variables : l’offre, la demande et le contexte. Le cadre combiné de l’emploi des connaissances pourrait servir dans l’étude de l’utilisation que font les enseignants de la recherche.